Electrochemical characterisations of ZnO nanowires for dye-sensitised solar cells. (5th April 2016) - Kanta, A.-F.; Schrijnemakers, A.; Decroly, A.
Abstract: Dye-sensitised solar cells (DSSCs) using fluorine-doped tin oxide (FTO) supporting substrate have been developed for fabricating zinc oxide (ZnO) nanowires film electrodes (anode). The ZnO nanowires were prepared by hydrothermal synthesis by varying process parameters such as the concentration of the seeding solution and the number of seed layers. The obtained electrodes were characterised by electrochemical impedance spectroscopy (EIS). The effects of seeds and dye solution soaking time were studied. The results show that charge transfer resistance (Rct ) decreases with increasing the number of seed layers, and with the dye solution soaking time, due to an increase of both the specific surface area and the coverage by the dye, respectively. In addition, it was found that dye solution soaking for 16 h maintains Rct at a low value (when measured under illumination) 72 h after assembling the DSSC. This indicates that there is no dye desorption after this time. Graphical abstract: Highlights: Zinc oxide nanowire arrays were produced by hydrothermal synthesis (seeding and growth of nanocrystallites) in aqueous medium. Charge transfer resistance decreases with the number of seed layers and dye solution soaking time.